KESANGGUPAN ALUMNI MENYUMBANG KEPADA UNIVERSITI: KAJIAN DALAM KALANGAN GURU-GURU MUSLIM DI JOHOR: Willingness of the Alumni to Contribute to their University: A Study among Muslim Teachers in Johor - Muhammad, Fidlizan; Abdul Razak, Azila; Mohd Hussin, Mohd Yahya; Awang, Salwa Amirah (Jurnal Syariah, 2014)
Charitable gift is virtuous in Islam. There are many factors that motivate an individual to donate. As far as Malaysian higher education is concerned, government has planned to grant autonomy to each university in which the latter is expected to generate their own income. One of the means for a university to generate its revenue is among other, the active involvement of the alumni in contributing their wealth to their former university. Therefore, this study aims to examine the factors that motivate an alumnus to contribute to a university. A total of 101 Muslim teachers are involved in this study. Willingness to contribute is measured by a mean score of 8 factors with 36 items. The findings have shown that the country’s management and economic status, relationship with the university and individual personality are among the most three important factors determining the willingness of alumni to contribute. On the other hand, the university information factor has the lowest mean score. In order to achieve the national policy goal, the university management should give their alumni a clear message about the need of alumni contributions for the sustainability of the university.